Geoelectric Investigation for Andesite Reserves Using Dipole-Dipole Configuration in Batursari Subdistrict, Pekalongan Regency, Central Java, Indonesia - Firdos Sidik; Kesya Fatihah; Wahyu Darmawangsa; Arifa Faza; Rizal Setiawan; Khakam Ma’ruf; Wahyu Hidayat; Wrego Giamboro (Iraqi Geological Journal)
Batursari District is a region in Pekalongan, Central Java that is rich in andesite rock resources. Andesite rock is an igneous rock widely used in infrastructure construction, such as split casts and foundations. The geoelectric method is one technique that can be used to identify the presence of andesite rocks. This method uses a dipole-dipole configuration of a geoelectric survey. For this research, 12 lines were used in the northwest-southeast direction, each with a length of 280 meters and 10 m spacing. Res2DinV and Rockworks software produce 2D cross-sections and 3D models for inversion processing. The 3D model was analyzed to determine the distribution of andesite rocks in the research area. Based on the inversion processing, resistivity values were interpreted as follows: 0-150 Ωm as soil, 150-250 Ωm as weathered andesite, 250-400 Ωm as partial weathered andesite, and ≥ 400 Ωm as fresh andesite. The 2D inversion analysis and 3D modeling showed that the fresh andesite was more abundant in the south and decreased in the north direction. The total volume of andesite rock in the research area was calculated as it is 28.683.000 m³ with a density of 2.60 tons/m³. The total andesite rock reserve was calculated to be 52.630.200 tons with an indicated calculation of 70%, equating to 20.078.100 m³ and a tonnage of 36.841.000 tons/m3.